Physico-chemical Studies and Thermal Decomposition Kinetics of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) Complexes of Vanillin-2-Aminothiazole - Sleema, B.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Manganese(II), cobalt(II), nikel(II), copper(II) and zinc(II) complexes of the Schiff base vanillin-2-aminothiazole have been synthesized. On the basis of spectral, magnetic and thermal data, octahedral structure was assigned to all complexes. Thermal decomposition of these complexes was studied by TG kinetic parameters, viz. activation energy E, pre-exponential factor A and order of reaction n were calculated from the TG curves using mechanistic and nonmechanistic integral equations.